The rôle of mitochondrial pyruvate transport in the stimulation by glucagon and phenylephrine of gluconeogenesis from L-lactate in isolated rat hepatocytes. - Thomas, A P (1981)
The sensitivity of glucose production from L-lactate by isolated liver cells from starved rats to inhibition by alpha-cyano-4-hydroxycinnamate was studied. A small percentage of the maximal rate of gluconeogenesis was insensitive to inhibition by alpha-cyano-4-hydroxycinnamate, and evidence is presented to show that this is due to pyruvate entry into the mitochondria as alanine. After subtraction of this rate, Dixon plots of the reciprocal of the rate of gluconeogenesis against inhibitor concentration were linear both in the absence and presence of glucagon, phenylephrine or valinomycin, each of which stimulated gluconeogenesis by 30-50%. Pyruvate kinase activity was decreased by glucagon, but not by phenylephrine or valinomycin. Inhibition of gluconeogenesis by quinolinate (inhibitor of phosphoenolpyruvate carboxykinase) or monochloroacetate (probably inhibiting pyruvate carboxylation) caused a significant deviation from linearity of the Dixon plot obtained with alpha-cyano-4-hydroxycinnamate. Amytal, however, inhibited gluconeogenesis without affecting the linearity of this plot. These data, coupled with a computer simulation study, suggest that pyruvate transport may control gluconeogenesis from L-lactate and that hormones may stimulate this process through an effect on the respiratory chain. An additional role for pyruvate kinase and pyruvate carboxylase is quite compatible with the data presented.